Perancangan User Experience Aplikasi Mobile Informasi Pajak dan Pembayaran Terpadu Kota Malang dengan Metode Human Centered Design - Eko Ardyanto; Herman Tolle; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The Regional Revenue Agency (Bapenda) of Malang City in its efforts to implement a smart city wants to create a mobile application for regional tax information. The application is expected to be a bridge between Bapenda and the community to make services and payments online through the application. Of course, the application needs to be well-made and easy to use so that people don't get confused when using the application. Based on this background, it is necessary to design a user experience for tax information and integrated payment mobile applications using the Human Centered Design (HCD) method. The research stage is carried out by determining user characteristics, identifying user needs, designing prototype and conducting tests. Identification of user characteristics and needs is done by creating empathy maps, personas and user journey maps. After that, for the designing prototype it is necessary to create a user flow and information architecture from the application. The design results are in the form of wireframes, screen flow and high-fidelity prototypes. Testing is done by assessing the effectiveness and efficiency aspects of usability. Based on the test results, the success rate is 91% and the time-based efficiency (TBE) is 0.15 goals / sec.